ANALYSIS OF LOGARITHMIC ANALOG-TO-DIGITAL CONVERTER WITH SUCCESSIVE APPROXIMATION TAKING INTO ACCOUNT PARASITIC CAPACITANCES - Szcześniak, Adam; Myczuda, Zynowij (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This article is a presentation of analysis of logarithmic analog-to-digital converter (LADC) with successive approximation taking into account parasitic capacitances of the converter. For the assumed parameters of converter structure, mathematical analysis with chosen capacitances of accumulative capacitors has been conducted. A criterion for choosing capacitances of accumulative capacitors has been determined.